THE EFFECTS OF COSTS OF PRODUCTION ON THE FINANCIAL PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES - NAKIGOZI FARIDAH (UGANDA CHRISTIAN UNIVERSITY, 2024)
The study aimed at examining the impact of costs of production on the financial performance of small and medium enterprises in Mukono. The study had several objectives which included; To establish the relationship between the costs of production and the financial performance of SMEs in Mukono. To find out how the costs of production affect the financial performance of small and medium enterprises. In the study, cross sectional research design was used on the quantitative data obtained from the questionnaire. Linear regression and correlation analysis were used to find out the relationship between the costs of production and the financial performance of small and medium enterprises. The study analyzed that there was a moderate negative correlation between costs of production and the establishment of new SMEs.
Keywords: under graduate dissertation.